THEORETICAL ASPECTS OF IMPROVEMENT OF NATIONAL LEGISLATION IN THE CONTEXT OF COUNTERING THE DESTRUCTIVE ACTIVITY OF AGENTS OF INFLUENCE - Калетнік, Василь Васильович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: analysis of foreign legislation in terms of improving national legislation to combat the destructive activities of agents of influence. Methods of research: general science, which provided an opportunity to explore issues of improving national legislation; statistical, inductive and deductive methods were used in the process of generalization and analysis of information; observation, theoretical generalization and historical method provided an opportunity to study the foreign experience of state and legal mechanisms to ensure national security of the state to combat the destructive activities of agents of influence (the experience of the United States, Russia, Israel, Australia, Hungary). Results: as a result of scientific research it is proved that the issue of increasing the functionality (achieving an adequate level of capabilities to meet real and potential threats) of state and legal mechanisms to ensure national security of Ukraine in terms of combating destructive activities of agents can be implemented by revising in regulations. In particular, a decision was proposed on the introduction in Ukraine of international practice to ensure transparent activities of public associations with foreign support (funding), as well as the introduction of additional categories of persons prohibited from holding positions related to state or local government, in case their adoption will help protect Ukrainian national interests. Emphasis is placed on further study of the activities of mass media financed from abroad, as well as the activities of foreign agents (agents of influence) in the supervisory boards of state unitary enterprises and companies, in the authorized capital of which more than 50 percent of shares belong state. Discussion: the dynamics of public relations and the development of the legal system of Ukraine, which are under the influence of today’s globalization processes, necessitate further scientific understanding of fundamentally new innovative approaches to improving national legislation in terms of combating the destructive activities of agents of influence.